THE MOTIF OF DREAMS IN KARAKALPAK FOLK EPICS - Kulimbetova Aysholpan Kuatbayevna (KONFERENSIYALAR, 2025)
Annotation. This article analyzes the peculiarities of the emergence and application of the dream motif in Karakalpak folk epics. The research studies the mythological and historical roots of the dream motif and reveals its role in the development of the epics’ plot. The research results demonstrate the unique characteristics of the dream motif in Karakalpak folk epics and its connection with the worldview and beliefs of the people.